2021
DOI: 10.3390/molecules26051240
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Stems Composition and Their Impact on Wine Quality

Abstract: Often blamed for bringing green aromas and astringency to wines, the use of stems is also empirically known to improve the aromatic complexity and freshness of some wines. Although applied in different wine-growing regions, stems use remains mainly experimental at a cellar level. Few studies have specifically focused on the compounds extracted from stems during fermentation and maceration and their potential impact on the must and wine matrices. We identified current knowledge on stem chemical composition and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 78 publications
8
33
1
Order By: Relevance
“…Table 2 shows the results of the spectrophotometric analysis performed on all samples. The antioxidant activity and TPC values were in the same order than those obtained by other authors [9,14,24]. As it can be seen, there exist significant differences in antioxidant activity, TPC and TF content among grape stems from different varieties in each vintage.…”
Section: Antioxidant Capacity Tf and Tpcsupporting
confidence: 77%
See 3 more Smart Citations
“…Table 2 shows the results of the spectrophotometric analysis performed on all samples. The antioxidant activity and TPC values were in the same order than those obtained by other authors [9,14,24]. As it can be seen, there exist significant differences in antioxidant activity, TPC and TF content among grape stems from different varieties in each vintage.…”
Section: Antioxidant Capacity Tf and Tpcsupporting
confidence: 77%
“…Usually, grape stems are used as organic fertilizer, as feed for ruminants [7] or valorized through the production of ethanol and paper pulp [8]. However, in recent years, several studies have demonstrated that these by-products contain high concentrations of polyphenols, cellulose, hemicellulose and lignin [9][10][11], which is causing a growing interest in their use as bioactive phytochemicals [12,13]. For instance, Leal et al [14] found that stem extracts present antimicrobial activity, with high efficacy against ulcers produced by Gram-positive bacteria in foot wounds.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Functionally, the antioxidant phenolic compounds are classified into secondary metabolites, a class of plant-derived compounds with diverse chemical structures and functions, which are produced during the physiological growth of grapevines or as their response to various forms of environmental stress [ 8 , 9 , 10 ]. Their presence in grapevines is associated with the quality and authenticity of wines [ 11 , 12 , 13 ] along with a broad spectrum of bioactivities including antimicrobial [ 14 , 15 ], anticancer [ 16 , 17 , 18 ], antiaging [ 19 ], antiglycogenic [ 20 ] and cardiovascular system-protective [ 21 , 22 ] properties. During the last three decades, the biological activities of grapevine phenolic compounds have been extensively exploited, providing valuable information that has attributed their health-benefitting effects to their strong antioxidant properties.…”
Section: Introductionmentioning
confidence: 99%